Test Of Various Bulbil Sizes And Dolomite Dosages On Porang (Amorphophallus muelleri Blume.) Growth In Peat Media - M. Amrul Khoiri; Anthony Hamzah; Muhammad Yudira; Ardian Ardian; Angga Pramana (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Porang plant (Amorphophallus muelleri Blume.) is one of the plants that have the potential to be cultivated in peatlands needed to increase its production. This study aims to increase the growth of smallholder plants on peat media until six months after planting through bulbil size with dolomite treatment. The research type was a 4x3 factorial experiment arranged based on a Completely Randomized Design (CRD). The first factor is bulbil size which consists of four levels, e.g., B1 (5.0 g-7.5 g), B2 (>7.5 g-10 g), B3 (>10 g-12.5 g), B4 (> 12.5 g-15.0 g) and the second factor dose of dolomite consists of three levels, e.g., D1 (2.5 ton.ha-1) D2 (5.0 ton.ha-1) D3 (7.5 ton.ha-1) -1). These two factors resulted in 12 treatment combinations, with three repetitions. Each experimental unit consisted of three plants. Parameters observed were growth power, plant height, stem diameter, crown width, rachis length, number of leaves, number of tillers, and number of tubers formed. The results showed that the application of dolomite could improve some of the chemical properties of peat soil. The bigger the bulbil size, the better the growth of people and the administration of 7.5 tons of dolomite.ha-1 increased several plant growth parameters such as growth power and plant height.